Center of mass trajectory length and performance in slalom - Moger, T.; Reid, R.; Tjørhom, H.; Giigien, M.; Haugen, P.; Kipp, R.; Smith, G. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Technique plays an important role in performance in alpine ski racing. Knowledge of technique is primarily anchored in the philosophies developed by experienced coaches and athletes. In recent years, a philosophy emphasizing a short and direct trajectory in slalom and giant slalom has gained popularity in coaching circles (Gartner, 2007). The purpose of this investigation was to evaluate this 'direct line" philosophy by quantifying the center of mass (COM) trajectory length and determining its relationship to performance for a given Situation in slalom.